Belief in conspiracy theories: Basic principles of an emerging research domain. (24th August 2018) - van Prooijen, Jan‐Willem; Douglas, Karen M.
Abstract: In this introduction to the EJSP Special Issue on conspiracy theories as a social psychological phenomenon, we describe how this emerging research domain has developed over the past decade and distill four basic principles that characterize belief in conspiracy theories. Specifically, conspiracy theories are consequential as they have a real impact on people's health, relationships, and safety; they are universal in that belief in them is widespread across times, cultures, and social settings; they are emotional given that negative emotions and not rational deliberations cause conspiracy beliefs; and they are social as conspiracy beliefs are closely associated with psychological motivations underlying intergroup conflict. We then discuss future research and possible policy interventions in this growing area of enquiry.